Viability improvement of Bifidobacterium animalis Bb12 by encapsulation in chitosan/poly(vinyl alcohol) hybrid electrospun fiber mats. (1st August 2020) - Mojaveri, Seyed Javad; Hosseini, Seyed Fakhreddin; Gharsallaoui, Adem
Highlights: B. animalis Bb12 loaded CS/PVA/INU fiber mats were fabricated via electrospinning. SEM and fluorescence imaging showed that viable cells were encapsulated in fibers. Thermal analysis of NFs proposed protection of probiotics in heat-treated foods. The survivability of probiotic in fiber mat was markedly enhanced under SGF and SIF. This research exhibits an efficient approach for synbiotic supplement preparation. Abstract: For the improvement of the probiotics' viability, a novel nanofiber mats consisting of chitosan (CS)/poly(vinyl alcohol) (PVA) loaded with the probiotic Bifidobacterium animalis subsp . lactis Bb12 and inulin (INU) as a prebiotic were fabricated via electrospinning approach. Scanning electron microscopy revealed that cells were well encapsulated in nanofibers with a diameter ranging from 117.5 ± 70.6 to 217.6 ± 62.7 nm and fluorescence microscopy images also revealed the viability of bacteria. Thermal analysis of fibrous mats proposed potential use of them in heat-treated foods owing to high melting temperatures (>200 °C). Moreover, in comparison to free cells, the survivability of cells especially enclosed in CS/PVA/INU electrospun fibers were remarkably increased under simulated gastric (SGF) and intestinal fluids (SIF). This study shows that the electrospun fiber mats are acceptable platforms for the protection of living probiotic cells and provide a substitute way for the expansion of functional food.